To Assess the Level of Knowledge Regarding Partogram among the Nursing Students in Selected Nursing College of Punjab (International Journal of Nursing Education, 2019)
Background of the Study: Excellent obstetrician and midwife must always be alert to detect any sign and symptoms of abnormal labor. Prolong labor presents a picture of mental anguish, physical morbidity and may need to emergency procedure and other surgical intervention1. The goal of this study is to use partogram to monitor labor, initiate uterine activity that is sufficient to produce cervical change and fetal descent while avoiding uterine hyperstimulation, hypostimulation and fetal distress and provide timely surgical intervention where required. Aim of the Study: The aim of the study is to assess the level of knowledge regarding partogram of nursing students in selected nursing colleges, Punjab. Material and Method: A quantitative research approach, descriptive study in which descriptive research design was used to conduct the research study. 60 nursing students of SINPMS, Badal were selected for the study with purposive sampling technique. A self structured knowledge questionnaire was used to assess the level of knowledge regarding partogram among nursing students. Result: the study depicted that out of 60 nursing students of SINPMS, Badal, 6(10%) have good level of knowledge followed by 41(68.3%) nursing students of SINPMS having average level of knowledge and the remaining 13(21.6%)nursing students of SINPMS having below average level of knowledge. So Average level of knowledge among Nursing students of SINPMS, Badal, Punjab. The overall mean 13.3 and SD is 6.82. Level of knowledge was significantly (p<0.5) not associated with age, gender, class, source of information. Conclusion: The study concluded that average level of knowledge among nursing students